Optimalisasi Sektor Pertanian melalui Penerapan Wakaf Berkelanjutan - Ahmad Muqorobin; Mahmudah Agustiyani (Proceedings of Annual Conference for Muslim Scholars, 2017)
Aplication of waqf in Indonesia are still traditional. This is evidenced by the laarge number of the waqf land still dormant or reserved only for worship. Whereas, in the land of the endowments are manage with good management and leads to the productive nature of it can help Indonesia’s developments in several sectors. According to the Minister of agriculture, agriculture land in Indonesia today many experienced a transfer of fungsion of the land. Therefor, the distribution of property including land endowments can be directed to development of the agricultural sector. The agricultural sector is one of the sectors of Indonesia’s economy so that the amplifier throughthe result of the sector can be developed for the contraction sector, such as education, health, economy and so on. So the necessary endowments that are sustainable in the management or sustainable agriculture in order to get maximum result and have an impact on development in other sectors. The writing of this paper use the data of the secondary with the study of librarianship with a qualitative description. In this paper also outline a SWOT analysis of the model of planning-based sustainable endowments.